Innovations in the Strategy of the European Union’s Economic Growth - Puślecki, Zdzisław W. (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2014)
The main aim of the paper is the presentation of the innovation system in the strategy of the European Union’s economic growth. According to the new theory of growth being the best theoretical foundation for the concept of the innovation system, the primary factor influencing the economic growth is the endogenous technological progress. To the particular goals of the research belong the presentation of the model of innovation system, theoretical concept of the innovation system and innovation process, constructed advantage, the Triple Helix model, Innovation Union, Europe 2020 strategy, Horizon 2020 as the financial instrument implementing the Innovation Union. The problems were researched by quantity and quality scientific methods. Utilised also, deduction and induction, statistic and prognostic methods. The important results of the research is the conclusion that in the innovation process also in the European Union very important are the connection between science, market (industry) and governance. There is positive dependence between innovation activity and effectiveness of the innovation process. The more interaction and cooperation it can observe on the regional level than on the state. The new programme of the Europe 2020 and Innovation Union are very important factors of the strategy the EU economic growth

Celem głównym artykułu jest przedstawienie roli innowacji w strategii wzrostu gospodarczego Unii Europejskiej. Zgodnie z nową teorią wzrostu będącą najważniejszą podstawą koncepcji systemu innowacyjnego, zasadniczym czynnikiem wzrostu gospodarczego jest endogeniczny postęp technologiczny. Do celów szczegółowych badania należały przedstawienie modelu systemu innowacyjnego, teoretycznej koncepcji systemu innowacyjnego i procesu innowacyjnego, korzyści strukturalnych powstających w regionie, modelu Potrójnej Spirali, Unii Innowacyjnej, strategii Europa 2020 oraz instrumentu finansowego Unii Innowacyjnej czyli Horyzontu 2020. Rozważane problemy były badane przy zastosowaniu metod jakościowej i ilościowej. Wykorzystano także metody dedukcji i indukcji oraz statystycznej prezentacji danych i prognozowania. Do najważniejszych rezultatów badań należy stwierdzenie, że w procesie innowacyjnym, także w Unii Europejskiej bardzo ważne są wzajemne powiązania między badaniami naukowymi, przedsiębiorstwami, czyli rynkiem i zarządzaniem na odpowiednich poziomach działalności gospodarczej. Występuje też pozytywna zależność między działalnością innowacyjną i efektywnością procesu innowacyjnego. Więcej wzajemnych interakcji i uwidacznia się przy tym na poziomie regionu niż na poziomie państwa. Nowe programy Europa 2020 i Unia Innowacyjna są niezwykle istotnymi czynnikami strategii wzrostu gospodarczego Unii Europejskiej
Innowacje w strategii wzrostu gospodarczego Unii Europejskiej
Keywords: technological progress; innovation system; innovation process; constructed advantage; Triple Helix model; Innovation Union; Horizon 2020; Europe 2020; economic growth